Teacher Efficacy, SWB The Relationship between Teacher Efficacy and Subjective Well-being among Special Education Teachers in Jakarta - Larasati, Audrey Mega; Monika, Monika (International Journal of Education, Information Technology, and Others, 2024)
Being a special education (SLB) teacher requires specialized skills and strong convictions to impart knowledge to students with diverse needs and characteristics. The belief that a teacher can successfully accomplish tasks is closely linked to self-efficacy. High self-efficacy makes one confident in controlling situations and achieving positive outcomes. Similarly, when a teacher strongly believes in their ability to teach students with special needs, they tend to feel more satisfied and happy with the results of their efforts in achieving educational goals. Special Education teachers (SLB) who struggle to fulfill their job tasks and responsibilities may impact their life satisfaction, emphasizing the importance of self-confidence in handling such tasks and responsibilities successfully. This research aims to investigate the relationship between teacher self-efficacy and subjective well-being (SWB) among SLB teachers. This correlational quantitative study utilized purposive sampling techniques and questionnaires through the g-form and surveys. The questionnaires used included the Teacher efficacy for measuring teachers' self-efficacy, as well as the Satisfaction with Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE) for assessing subjective well-being (SWB). The study involved 234 SLB teacher participants in Jakarta, aged 20 to 65 years. The research was conducted over approximately two months, from October 2023 to November 2023. Pearson correlation test results indicate a positive relationship between self-efficacy and the subjective well-being of teachers, with r = 0.48. This suggests that higher self-confidence is associated with a positively perceived personal state.